A Review of Ectoparasitic Fungi Associated With Termites. (30th April 2021) - Wilson, Megan; Barden, Phillip; Ware, Jessica
Abstract: Termites and ectoparasitic fungi have been at odds for millions of years. Surprisingly, fungi rarely kill their host and termites are continuously parasitized, albeit at low rates. 'Termitophilous' fungi have succeeded in the difficult task of infiltrating the ecological fortress of social immunity that is the termite colony. Here we review 34 definitive ectoparasitic fungal species from nine genera specialized to infest the cuticle of 50 + termite species. In general, reports of fungal ectoparasites on termites are underestimated and the actual prevalence of infestation is likely much greater in nature. In this review, we synthesize >120 yr of reports and studies on ectoparasitic fungi and their termite hosts to present an update to where our knowledge rests and where the proceeding steps should be focused. In reviewing this material, we aim to unite knowledge from two disciplines, entomology and mycology, creating a literary source useful for entomologists and mycologists alike. We provide a comprehensive summary of all fungal genera, illustrations showing morphological distinctions and development on the termite host, a glossary of mycological terminology, and an updated chart of the biogeography of these groups. Additionally, we provide a phylogenetic summary of parasite lineages and their known hosts as well as the first review of molecular evidence obtained from these fungal species.